Coordination mechanism of construction industry supply chain based on data elements - Hong Zhang (PLoS ONE, 2025)
This paper presents a comprehensive approach to enhancing the coordination of the construction industry supply chain by incorporating data elements into the decision-making process. A two-level supply chain model is developed, consisting of a core enterprise and suppliers, initially analyzed in a non-contractual environment. The findings reveal inefficiencies in supply chain coordination under these conditions, prompting the design of a cost-sharing and profit-sharing contract model. By applying these contracts, supply chain coordination is significantly improved, leading to enhanced collaboration, optimized resource allocation, and increased profitability for all stakeholders. The innovative contribution of this research lies in its integration of data elements with contractual coordination mechanisms, which is verified through practical case studies and numerical simulations, offering a novel perspective and methodology for managing construction industry supply chains.